The Impact of Knowledge Management on Strategic Entrepreneurship: A Field Study at Yemeni Private Universities in the Capital Municipality of Sana'a - Majed Kassem Abdu Al-Sayani; Somaia Abdelwareth Al-Qadasi (University of Science and Technology, Sana’a, Yemen, 2025)
The study aimed to measure the level of knowledge management practices and the level of strategic leadership achievement in private Yemeni universities in the Capital Municipality of Sana'a, as well as to assess the impact of knowledge management on strategic leadership in these universities. The study employed a descriptive analytical approach and relied on a questionnaire as a data collection tool. A comprehensive enumeration method was used for the study population, which comprised 367 leaders. Data were analyzed using statistical methods such as means, standard deviations, percentages, Cronbach's alpha reliability coefficient, one-way ANOVA, and simple regression analysis, utilizing the Statistical Package for the Social Sciences (SPSS) to test the validity of the study hypotheses. The study found that the level of knowledge management practices in the universities under study was high, and the level of strategic leadership achievement was also high. It was concluded that there is a statistically significant impact of knowledge management on strategic leadership in the universities studied, with the knowledge distribution dimension having the most significant effect on strategic leadership, followed by the knowledge application dimension, then the knowledge generation dimension, while the knowledge storage dimension had the least effect. The study recommends enhancing the level of knowledge management practices in private universities in the Capital Municipality of Sana'a and promoting a culture of strategic entrepreneurship by creating a work environment that fosters creativity, innovation, and risk-taking.